Nutrient delivery - Grumezescu, Alexandru Mihai (Nanotechnology in the agri-food industry, 2017)
This book discusses the fabrication, merits, demerits, applications, and bioavailability enhancement mechanisms of various nanodelivery systems. Recent developments in various nanodelivery systems are also highlighted.